LINEAMIENTOS DE ERGONOMÍA Y PREVENCIÓN DE RIESGOS LABORALES, PARA LA MEJORA CONTINUA EN EL DEPARTAMENTO DE EMERGENCIA DE UN SERVICIO MÉDICO-ASISTENCIAL (2014)
One problem that continues to recur in the working population of medical care services is related to the lack of knowledge about health and safety conditions that must be considered for the development of its activities, which means that much of the diversity of hospital workers in addition to performing their jobs, knowing the basics of ergonomics and occupational risk prevention (PRL), without regard to the consequences that this may cause you. This has contributed, among other problems, the risk exposure of their activities intensified, whereby the occurrence of incidents and accidents is more sensible, in addition to the predisposition to occupational diseases and other problems of pollution in general. In contribution to the solution of this problem, the objective of this research is to establish guidelines for ergonomics and occupational risk prevention for continuous improvement in the emergency department of a medical-care service. It is a field that developed in a hospital of high complexity, being descriptive, transactional, non- experimental design, considering the convenience sample. The data collection instrument was the record of systematic observation, designed for the assessment of the physical and spatial, environmental, complementary service aspects and risk factors in general. The result provided an enlightened view of the functions of the departments of medical emergency with the risks associated with the work of the same, from which the guidelines that keep into consideration aspects of Ergonomics and PRL from planning were designed for development of its activities, ensuring the sustainability of the production process.